2014
DOI: 10.1116/1.4901505
|View full text |Cite
|
Sign up to set email alerts
|

Negative gate-bias instability of ZnO thin-film transistors studied by current–voltage and capacitance–voltage analyses

Abstract: Effects of negative gate-bias stress on the electrical properties of ZnO thin-film transistors (TFTs) are investigated. Under negative gate-bias stress, the ZnO TFTs exhibit higher carrier mobility, larger OFF-state current, and a negative shift in threshold voltage with no significant change in subthreshold slope. The time dependence of threshold-voltage shift on various bias stress conditions can be described by a logarithmic equation. Based on the analysis of hysteresis behaviors in current-voltage and capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…We observed that the shifted characteristics curves returned freely to their original positions after relaxation time of 4 hours in air at room temperature following a 10 4 s stress time. This suggests that charge trapping at or near the interface in the semiconductor is the dominant mechanism responsible for the instability [27]. It has been shown that ZnO TFT performance parameters (μ eff , V T and V On ) are affected by ZnO active layer thickness.…”
Section: Zno Thicknessmentioning
confidence: 99%
“…We observed that the shifted characteristics curves returned freely to their original positions after relaxation time of 4 hours in air at room temperature following a 10 4 s stress time. This suggests that charge trapping at or near the interface in the semiconductor is the dominant mechanism responsible for the instability [27]. It has been shown that ZnO TFT performance parameters (μ eff , V T and V On ) are affected by ZnO active layer thickness.…”
Section: Zno Thicknessmentioning
confidence: 99%